Gender Transformative Methodologies CoP. #Masculinities #Conversation 3 - Male involvement in ending gender violence - Banda, Nelson; Akamandisa, Vincent; Farnworth, Cathy Rozel; Bailey, Arwen (2025)
In this conversation, Nelson Banda and Vincent Akamandisa, both of the Zambian National Men’s Network, share reflections on their considerable experience working with men and boys. In particular, the conversation focuses on Male Involvement in Ending Gender Violence, reflecting on how men are affected by gender violence, and on men's health.